2009
DOI: 10.1007/s10750-009-9846-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium on charophytes calcification: implications for phosphorus speciation stored in biomass and sediment in Myall Lake (Australia)

Abstract: We examined the effect of magnesium (Mg) on the charophytes calcite (CaCO 3 ) encrustation and assessed whether charophytes, growing on non-calcareous sediments in the Myall Lake, a poorly flushed shallow coastal lake with salinity of 2-3 PSU, could function as an effective nutrient sink for phosphorus (P) in a similar manner to charophytes growing on calcareous sediments of the freshwater calcium (Ca)-rich hardwater, i.e., through the formation of Ca-bound P. Our results showed that high Mg in the Myall Lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…However, that would only be the case if aragonite was precipitated. Second, according to the previous study in Lake Jasne (Pukacz et al 2014a), favourable conditions for calcite precipitation occurred; thus, the correlation may be the effect of the inhibiting role of magnesium ions in the process of calcification, as suggested by Siong and Asaeda (2009). …”
Section: Discussionmentioning
confidence: 80%
“…However, that would only be the case if aragonite was precipitated. Second, according to the previous study in Lake Jasne (Pukacz et al 2014a), favourable conditions for calcite precipitation occurred; thus, the correlation may be the effect of the inhibiting role of magnesium ions in the process of calcification, as suggested by Siong and Asaeda (2009). …”
Section: Discussionmentioning
confidence: 80%
“…McConnaughey, 1991;McConnaughey and Falk, 1991), phosphorus assimilation (e.g. McConnaughey and Whelan, 1997;Siong, 2006;Siong and Asaeda, 2009b) and hyper-accumulator of heavy metals (McConnaughey, 1991;Siong and Asaeda, 2009a). In mildly alkaline water, DIC decreased by two means, either was taken up by the photosynthesis of the algae or became incorporated in the cell wall of Chara by calcification (Ray et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, besides the indirect mechanism above, P in the water column was also directly co-precipitated with encrusted calcite along the charophyte intermodal cell, and such a calcification should be regarded as a positive feedback in stabilizing Chara dominance in lakes. Siong & Asaeda (2009) studied the effect of Mg on the charophyte calcite encrustation, and assessed whether charophytes growing on the noncalcareous sediments of the Myall Lake could function as an effective nutrient sink for P in a similar manner to charophytes growing on the calcareous sediments of freshwater calciumrich hard water systems. According to the last authors, calcification of Chara fibrosa was significantly inhibited by Mg in the water column and, consequently, reduced the formation of Ca-bound P that has a potential sink for P. However, a large percentage of nonbioavailable forms of P in the lake sediments suggested that P sink was through burial of dead organic matter and subsequent mineralization process.…”
Section: Nutrientsmentioning
confidence: 99%